Key heterocycle cores for designing multitargeting molecules - Silakari, Om (Elsevier, 2018)
Key Heterocycle Cores for Designing Multitargeting Molecules provides a helpful overview of current developments in the field. Following a detailed introduction to the manipulation of heterocycle cores for the development of dual or multitargeting molecules, the book goes on to describe specific examples of such developments, focusing on compounds such as Benzimidazole, Acridine, Flavones, Thiazolidinedione and Oxazoline. Drawing on the latest developments in the field, this volume provides a valuable guide to current approaches in the design and development of molecules capable of acting on multiple targets. Adapting the heterocyclic core of a single-target molecule can facilitate its development into an agent capable of acting on multiple targets. Such multi-targeting drugs have the potential to become essential components in the design of novel, holistic treatment plans for complex diseases, making the design of such active agents an increasingly important area of research.